2022
DOI: 10.3390/ijerph191912914
|View full text |Cite
|
Sign up to set email alerts
|

Burnout in Intensive Care Nurses during the COVID-19 Pandemic: A Scoping Review on Its Prevalence and Risk and Protective Factors

Abstract: Background: The COVID-19 pandemic has strained hospitals and healthcare workers engaged in combating the virus with limited knowledge and resources. Intensive care unit (ICU) nurses are among the healthcare workers most affected by the pandemic and are at risk for developing burnout syndrome. Objective: The present study aims to explore burnout symptoms prevalence among ICU nurses and to identify the individual, organizational, and contextual risk, and protective factors of burnout in ICU nurses during the COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2
15

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
1
26
2
15
Order By: Relevance
“…In short-lived disasters, this strategy has proven it's worth [11]. However, the COVID pandemic has shown that there may be a very steep price to pay when such an approach is taken over long periods of time: psychopathologies, which may express both during the acute phase [12,13] and after the event [14][15][16]17 & ]. In terms of space and equipment, one may use the ICU as an excellent model for highlighting the difficulties of determining what resources are needed.…”
Section: What Resources Require Allocation?mentioning
confidence: 99%
“…In short-lived disasters, this strategy has proven it's worth [11]. However, the COVID pandemic has shown that there may be a very steep price to pay when such an approach is taken over long periods of time: psychopathologies, which may express both during the acute phase [12,13] and after the event [14][15][16]17 & ]. In terms of space and equipment, one may use the ICU as an excellent model for highlighting the difficulties of determining what resources are needed.…”
Section: What Resources Require Allocation?mentioning
confidence: 99%
“…The present study aimed to compare burnout levels in Italian nurses engaged in the front line of patients' care suffering from COVID-19 (ICU R.Ns, ED R.Ns, R.Ns working in isolation), during the first (from 11 February 2020 to 11 June 2020) and the second waves (from 14 September to 31 December 2020) [30] of the COVID-19 pandemic, by investigating any differences in burnout levels according to gender and years of work experience.…”
Section: Aimmentioning
confidence: 99%
“…During the COVID-19 pandemic, higher values of burnout (roughly 27.3%) were reported all around the world: from Italy [23] to the USA [24], from Germany [25] to Saudi Arabia [26], by referring also to specific socio-demographic variables, such as gender, as females reported higher levels in all the three dimensions of burnout [1] and years of work experience, as nurses who have more years of work experience are more exposed to all risk factors associated with burnout syndrome and then, to develop it [27][28][29]. Additionally, high levels of burnout (emotional exhaustion, depersonalization, and reduced personal accomplishment) were recorded mostly among nurses employed in the intensive care unit (ICU) during the pandemic [30], also associated with high scores of anxiety and insomnia levels, too [29]. The rising trend was influenced by several factors, like: increased workload, deficiencies in personal protective equipment, individual and social stigma linked to the SARS-CoV-2 infection, fear of contagion [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, ‘Third Global Forum on Human Resources for Health’ estimates that by 2035, the nursing deficit will reach 12.9 million [ 2 , 3 ]. Although the worldwide pandemic of COVID-19 has improved the popularity of the nursing profession in the public eye [ 4 ], it has also led to more burnout among nurses [ 5 , 6 ], which may increase turnover. Consequently, this shortage is becoming an international problem and one of the main factors determining future world health policy [ 1 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the worldwide pandemic of COVID-19 has improved the popularity of the nursing profession in the public eye [ 4 ], it has also led to more burnout among nurses [ 5 , 6 ], which may increase turnover. Consequently, this shortage is becoming an international problem and one of the main factors determining future world health policy [ 1 , 6 , 7 ]. It has been suggested that building an appropriate public image of the nursing profession may provide a solution to the nursing shortage [ 1 , 8 10 ].…”
Section: Introductionmentioning
confidence: 99%